Awareness of green it among students and lecturers in FKSM / Muhammad Hatta Zulkifly - Zulkifly, Muhammad Hatta (2012)
Information Technology (IT) is at the heart of every successful modem business. Without it, success is impossible. Although Information Technology helps us in so many ways in our everyday life, yet there are some problems associated with it. Global warming and other environmental issues such as energy and resource constraint become major problems nowadays, the total electrical energy consumption by servers, computers, monitors, data communications equipment, and cooling systems for datacenters is steadily increasing.